Interworking of protocols in IPv6 mobility management - Ong, Bi-Lynn; Hassan, Suhaidi (2007)
During communication between wireless users, disconnection may occur during the handover process. The high handover latency during the process of handover degrades the service quality of the wireless communications.This problem becomes more crucial if the operation network is transmitting real-time multimedia applications.This paper presents our work on the interworking of protocols in IPv6 mobility management which aims to explore the means to reduce the handover latency.We propose SIP over IPv6 mobility management with hybrid mechanism which we believe has the possibility to reduce the handover latency.The newly proposed protocol is developed and compared with the existing protocols.The result of the simulation experiment shows that our proposed protocol performs better compared to other protocols.